(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the results of preoperative preparation, anesthesia and surgical treatment of patients operated on for non-toxic nodular goiter intensive care, acute coronary syndrome. A new approach to preoperative preparation for thyroid surgery is described. The effectiveness in the preoperative period of using the modified method of preoperative preparation using sibazon and droperidol and anesthesia with the use of ketamine and the advantages of this method compared with other methods of general anesthesia are shown.